An age- and sex-dependent role of catecholaminergic neurons in the control of breathing and hypoxic chemoreflex during postnatal development - Patrone, Luis Gustavo A. [UNESP]; Capalbo, Aretuza C. [UNESP]; Marques, Danuzia A. [UNESP]; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Elsevier, 2020)
The respiratory system undergoes significant development during the postnatal phase. Maturation of brainstem catecholaminergic (CA) neurons is important for the control and modulation of respiratory rhythmogenesis, as well as for chemoreception in early life. We demonstrated an inhibitory role for CA neurons in CO2 chemosensitivity in neonatal and juvenile male and female rats, but information regarding their role in the hypoxic ventilatory response (HVR) is lacking. We evaluated the contribution of brainstem CA neurons in the HVR during postnatal (P) development (P7-8, P14-15 and P20-21) in male and female rats through chemical injury with conjugated saporin anti-dopamine beta-hydroxylase (DβH-SAP, 420 ng·μL−1) injected in the fourth ventricle. Ventilation (V̇E) and oxygen consumption were recorded one week after the lesion in unanesthetized rats during exposure to normoxia and hypoxia. Hypoxia reduced breathing variability in P7-8 control rats of both sexes. At P7-8, the HVR for lesioned males and females increased 27% and 24%, respectively. Additionally, the lesion reduced the normoxic breathing variability in both sexes at P7-8, but hypoxia partially reverted this effect. For P14-15, the increase in V̇E during hypoxia was 30% higher for male and 24% higher for female lesioned animals. A sex-specific difference was detected at P20-21, as lesioned males exhibited a 24% decrease in the HVR, while lesioned females experienced a 22% increase. Furthermore, the hypoxia-induced body temperature reduction was attenuated in P20-21 lesioned females. We conclude that brainstem CA neurons modulate the HRV during the postnatal phase, and possibly thermoregulation during hypoxia.
Keywords: Adrenergic and noradrenergic neurons; Catecholamine; Chemosensitivity; Development; Medulla; Pons